THE RIGHT OF CHILDREN TO BE HEARD IN CROATIAN CIVIL LAW (EU and comparative law issues and challenges series (ECLIC), 2024)
The active involvement of a person in court proceedings is essential for his effective participation and is a reflection of his right to be heard. The right to be heard is one of the basic procedural rights, which implies that a person should be allowed to express his concerns as well as his experience that what he said has be taken into account in the decision-making process. Competent authorities are obliged to listen to the participants in the procedure and talk with them, not about them. Although in some situations this will be difficult and incomprehensible, especially in relation to children or persons deprived of legal capacity, everyone capable of expressing their will and preferences in some way needs support to facilitate that expression. That is, to every person should be made possible to participate in court proceedings in such a way that they can influence its outcome by articulating their will. In this paper, we will analyze the child's right to be heard and express his opinion, and in this regard, we will warn about the inconsistency of the provisions of the Croatian general procedural regulation - the Law on Civil Procedure with the provisions of the Croatian Family Law, as well as international regulations and practice. We will refer to the question of the procedural legitimation of the child in court proceedings in which his rights are decided. Also, we will analyze the issue of the procedural legitimation of a child in family law disputes, in which the individual rights of the child are adhesivelly decided in accordance with the principle that everyone should have the opportunity to actively participate in the litigation that is conducted about his rights and interests.